Gratitude Therapy to Improve Self Esteem of Adolescents with Body Dysmorphic Disorder Tendencies - Cahyaning Suryaningrum; Syaripah Aini; Ni’matuzahroh; Taufik (Universitas Muhammadiyah Surakarta, 2025)
Some adolescents experience dissatisfaction when their bodies undergo unwanted changes. They will develop an exaggerated negative self-image that leads to body dysmorphic disorder (BDD). The negative image that adolescents with BDD tendencies have of themselves is not only limited to their appearance but has extended to their whole self. Some adolescents with BDD tendencies experience self esteem problems. This study aims to determine the effect of gratitude therapy on self esteem in adolescents with BDD tendencies. The subjects in this study amounted to 8 people selected by purposive sampling technique. Subjects in this study are adolescents aged 15-18 years and have dissatisfaction with certain body parts. This type of research is a two group randomized pretest-posttest control group design with instruments in the form of a body dysmorphic disorder tendency scale and Rosenberg self esteem scale. The data in this study were analyzed using the Wilcoxon test and the Mann Whitney test. The results showed that gratitude therapy can increase self esteem in adolescents with BDD tendencies. This can be seen from the results of the Mann Whitney test which shows a value of Z = -2.021 (p = 0.043 <0.05). Therefore, it can be concluded that gratitude therapy can increase self esteem in adolescents with BDD tendencies.